Analysis of Life Insurance Premium in Regard to Net Income as an Influencing Factor– the Case of the Republic of Serbia - Munitlak Ivanović, Olja; Raspopović, Neda; Mitić, Petar; Rakić, Slobodan (Industrija, 2013)
In current business conditions, insurance market in the Republic of Serbia notes positive but relatively slow growing trend. During the last few years, life insurance market in Serbia has an upward trend, however, it still significantly falls back in comparison to developed European countries. Insufficient development of life insurance sector is in direct relation to insufficient economic development, weak financial market, high unemployment rate and poor implementation of economic reforms. Additionally there is a problem due to the lack of both quality and quantity of education with insufficient basic knowledge of potentials that this type of insurance offers. The aim of this paper is to present the projection of life insurance premium on the basis of linear trend parameters and correlation degree between average net income and the amount of life insurance premium and to emphasize the necessity of intense development of life insurance market.